PENGARUH KEADILAN ORGANISASI BUDAYA ORGANISASI DAN KEPUASAN KERJA PEGAWAI TERHADAP KOMITMEN ORGANISASIONAL PADA INSPEKTORAT DAERAH KABUPATEN BANGLI - Mursani, Ni Nyoman; Sudiyani, Ni Nyoman (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
Organizational justice, organizational culture and job satisfaction are aspects that influence employee organizational commitment. The Bangli District Inspectorate focuses on and recognizes cases related to organizational justice, organizational culture, and job satisfaction in an effort to increase employee organizational commitment. The number of doodles was determined as a bored doodle program of 49 employees without inspectors and researchers because the researchers were assigned to the Bangli District Inspection Office. The results of the research confirm that organizational justice, organizational culture and job satisfaction have a positive and significant impact on the organizational commitment of the Bangli District Oversight Office employees either simultaneously or in combination.